DEVELOPMENT AND OPTIMIZATION OF RABEPRAZOLE CHRONO-MODULATED DRUG DELIVERY SYSTEMS - KURAPATI, PHANEENDRA; CHINNI, SANTHIVARDHAN (International Journal of Applied Pharmaceutics, 2024)
Objective: Development and optimization of chrono-modulated pulsatile drug delivery systems (CPDDS) loaded with Rabeprazole for treating nocturnal acid breakthrough in ulcer patients was set as the major objective of this work. Methods: CPDDS were developed to provide drug release as two pulses with predetermined gap. Separate microparticles for delayed instant release (DIR) and delayed extended-release (DER) were formulated. Through the optimization of several formulation and process parameters, ER microparticles were created as matrix microspheres. Central composite design was used to understand how the factors affected the responses. The optimized ER microspheres and plain drug were separately subjected to enteric coating to obtain DER and DIR portion microparticles, respectively. Results: With the exception of stirring speed's impact on drug release, every other factor was found to have a significant influence (p<0.05) on every response. The mechanism underlying the Rabeprazole's delayed prolonged release was explained by the SEM images. The microspheres made with Eudragit RSPO at 0.72 g and polyethylene oxide at 0.5 g for 1 g of Rabeprazole at 400 rpm were shown to be the optimal formulation based on the graphical optimization results. After being coated with a terminal enteric coating, this formulation showed delayed release for a duration of 6 h. Conclusion: After oral administration of equal doses of DIR microcapsules along with the optimized DER microspheres could release Rabeprazole effectively as two different pulses at the desired time intervals.